Squamous Cell Carcinoma of the Pancreas - De Souza, Andre Luiz; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2014)
No abstract available. Image: Metrowest Medical Center (Framingham, MA, USA) logo.